pengaruh PENGARUH AGENCY COST OF FREE CASH FLOW DALAM PENGAMBILAN KEPUTUSAN MANAJEMEN PERUSAHAAN DALAM MENERBITKAN SUKUK - Fatmala, Angelica Nadia (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Sukuk is one of the funding instruments that companies can use to obtain funds for investment projects in the future. Sukuk were first issued by companies in Indonesia in 2004 with high interest from creditors so that in 2017 the total number of sukuk issued by companies reached 137. Previous research has proven that sukuk can be one of the policies carried out by companies to reduce the agency cost of free cash flow. Research in Malaysia found that companies that face the agency cost of free cash flow tend to issue sukuk rather than bonds to minimize the agency cost of free cash flow. Research related to agency cost of free cash flow and tribal funding decision making in Indonesia is still very limited. Therefore, research was conducted regarding the effect of the agency cost of free cash flow on the company's decision to issue sukuk rather than bonds. The number of samples used in this study were companies that had issued sukuk from 2004 to 2017. After the data was collected and selected, 106 data on the issuance of sukuk and bonds were used with clear information. Based on the results of logistic regression, it is known that companies experiencing agency costs of free cash flow do not choose to issue sukuk over bonds. The results of this study are different from the results of studies in Malaysia which show significant results. This shows that the majority of companies in Indonesia still do not understand the benefits of sukuk in reducing the agency cost of free cash flow, so that the issuance of sukuk is used more as a funding diversification to reduce the risk of failure. Keywords: Sukuk, Bonds, Financing, agency cost of free cash flow, logistic regression